Increased instruction time and stress-related health problems among school children - Jan Marcus; Simon Reif; Amelie Wuppermann; Amélie Rouche (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
While several studies suggest that stress-related mental health problems among school children are related to specific elements of schooling, empirical evidence on this causal relationship is scarce. We examine a German schooling reform that increased weekly instruction time and study its effects on stress-related outpatient diagnoses from the universe of health claims data of the German Social Health Insurance. Exploiting the differential timing in the reform implementation across states, we show that the reform slightly increased stress-related health problems among school children. While increasing instruction time might increase student performance, it might have adverse effects in terms of additional stress.
Keywords: I18; I28; 330; stress; mental health; instruction time; G8 reform